Pemanfaatan Bakteri Endofit pada Pisang untuk Mengendalikan Penyakit Darah: Isolasi, Uji Penghambatan In Vitro dan In Planta - Abdjad Asih Nawangsih (Institut Pertanian Bogor, 2007)
Blood desease caused by blood disease bacterium is one of the important disease of banana in Indonesia. Disease control using resistant varieties was difficult to be practiced because the pathogen can attack all varieties of banana. Sanitation and eradication has been done by farmers but the desease still occured in the field with high incidence. Aplication of same rhizosphere bacteria failed to control the desease in the field.Keyword: Bacillus spp., Pseudomonas spp., endophytic bacteria, blood disease bacterium, banana